Revitalizing quality of life: a case report on the beneficial impact of comprehensive rehabilitation therapy in treating upper-limb lymphedema following breast cancer surgery - Sui, Yan-Fang; Tong, Lang-Qian; Lin, Xia-Fei; Wu, Hai-Xia; Shi, Jing-Qin; Wang, Shan-Shan; Tang, Bu-He; Song, Zhen-Hua (Frontiers in Oncology, 2023)
Objective: To underscore the paramount significance of incorporating comprehensive rehabilitation therapy as a crucial aspect of managing lymphedema caused by breast cancer surgery, and to illuminate our first-hand experience and insights gained in utilizing this approach. Methods: We present a case report of a breast cancer survivor who had been suffering from persistent left upper-limb edema for over 15 years, who was effectively treated with a combination of conventional rehabilitation (seven-step decongestion therapy) and a comprehensive rehabilitation program (seven-step decongestion therapy, along with core and respiratory function training, as well as functional brace wearing). The efficacy of the rehabilitation therapy was evaluated through a comprehensive assessment Results: Although the patient underwent the conventional rehabilitation program for one month, only limited improvement was observed. However, after an additional month of comprehensive rehabilitation treatment, the patient exhibited significant improvement in both lymphedema and the overall function of the left upper limb. The patient's progress was quantified by measuring the reduction in arm circumference, which demonstrated a notable decrease. Furthermore, improvements in joint range of motion were observed, with forward flexion of the shoulder enhancing by 10°, forward flexion improving by 15°, and elbow flexion increasing by 10°. In addition, manual muscular strength tests revealed an increase in strength from Grade 4 to Grade 5. The patient's quality of life was also significantly improved, as evidenced by the increase in the Activities of Daily Living score from 95 to 100 points, the increase in the the Functional Assessment of Cancer Therapy: Breast score from 53 to 79 points, and the decrease in the Kessler Psychological Distress Scale score from 24 to 17 points. Conclusions: While seven-step decongestion therapy has been shown to be effective in reducing upper-limb lymphedema caused by breast cancer surgery, it has limitations in treating more chronic cases of the condition. However, when combined with core and respiratory function training and functional brace wearing, seven-step decongestion therapy has been shown to be even more effective in reducing lymphedema and improving limb function, ultimately leading to significant improvements in quality of life.